Writing a book review - Peh, W.C.G.; Ng, K.H. (Singapore Medical Assoc, 2010)
A book review is a form of academic writing that provides a succinct yet critical analysis evaluating the content, style, merit and significance of a book. The reader should gain insight into the strengths and weaknesses of the book, aided by input from the reviewer. The four stages of writing a book review are: introducing the book, outlining its contents, highlighting parts of the book by selecting particular chapters or themes, and giving a detailed evaluation.